COMPETENCIAS DIGITALES EN LOS ESTUDIANTES DEL PRIMER SEMESTRE DE LAS CARRERAS DE PEDAGOGIA DE LAS CIENCIAS EXPERIMENTALES, PERIODO ABRIL 2019 – AGOSTO 2019. - Chillogallo Corte, Jessica Nataly (2020)
The purpose of this research was to determine the level of digital skills in freshman students from the university, in the Pedagogy of Experimental Sciences: Mathematics and Physics, Chemistry and Biology and Computer science, with a total of 83 students. The research design was non-experimental, descriptive and field type since the observation occurred directly in the university context. To collect the data, a survey developed in google forms based on an instrument developed and validated by the European Union and the Council of Europe was applied. The results that were found show that the majority of students have developed a basic proficiency level, and there are very few students who reach the intermediate level, which states that freshman students from the university have not achieved their necessary digital skills to face university life, as a recommendation it is proposed that the authorities of the National University of Chimborazo should plan activities to develop these skills in a way that allows them to facilitate learning within the university environment and outside it, also provide an efficient relationship between teacher and student.